2022
DOI: 10.3390/antiox11071409
|View full text |Cite
|
Sign up to set email alerts
|

Factors Involved in Endothelial Dysfunction Related to Angiogenic Disbalance and Oxidative Stress, in Women at High Risk of Term Pre-Eclampsia

Abstract: Oxidative and inflammatory stress, angiogenic imbalance, and endothelial dysfunction are pathophysiological mechanisms occurring in pre-eclampsia (PE) that may persist over time and predispose women to a higher risk of cardiovascular disease (CVD) in the future. However, there is little evidence on the vascular function of women at risk of PE who have not developed the disease. The main objective of this research is to study factors and biomarkers involved in endothelial dysfunction related to oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Under normal conditions, the endothelium regulates vascular homeostasis by maintaining blood fluidity, nutrient trafficking, vasomotor tone, angiogenesis, and other processes 23 . The pathological process leading to endothelial cell dysfunction is very complex, including oxidative stress, angiogenic growth factor imbalance, vascular tone regulator molecules, and other factors 24 . Sepsis can alter endothelial permeability and the vasomotor response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal conditions, the endothelium regulates vascular homeostasis by maintaining blood fluidity, nutrient trafficking, vasomotor tone, angiogenesis, and other processes 23 . The pathological process leading to endothelial cell dysfunction is very complex, including oxidative stress, angiogenic growth factor imbalance, vascular tone regulator molecules, and other factors 24 . Sepsis can alter endothelial permeability and the vasomotor response.…”
Section: Discussionmentioning
confidence: 99%
“… 23 The pathological process leading to endothelial cell dysfunction is very complex, including oxidative stress, angiogenic growth factor imbalance, vascular tone regulator molecules, and other factors. 24 Sepsis can alter endothelial permeability and the vasomotor response. These changes have been observed in animal models of sepsis as well as in human tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms may contribute to ED, and numerous studies have reported risk factors for the occurrence and development of ED 6. Endothelial dysfunction, a major cause of ED, is thought to be associated with inflammatory and oxidative stress levels 7. Many vascular endothelial damage-associated diseases, such as cardiovascular disease (CVD)8 and type 2 diabetes, share this common pathological mechanism with ED 9.…”
Section: Introductionmentioning
confidence: 99%
“… 6 Endothelial dysfunction, a major cause of ED, is thought to be associated with inflammatory and oxidative stress levels. 7 Many vascular endothelial damage-associated diseases, such as cardiovascular disease (CVD) 8 and type 2 diabetes, share this common pathological mechanism with ED. 9 Therefore, ED is a harbinger of the severe development of these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, superoxide dismutase (SOD) is an important antioxidant that protects tissue from oxidative damage and can protect blood vessels from ROS damage and maintain vascular function ( 14 ). SOD is significantly decreased in endothelial cell injury diseases ( 15 , 16 ). A meta-analysis of 2,953 PE pregnant women and 3,621 healthy pregnant women found that a total of 26 studies described the SOD level of 739 PE pregnant women and 906 healthy pregnant women.…”
Section: Introductionmentioning
confidence: 99%